#### Answer

$-\frac{4}{3}$

#### Work Step by Step

$\frac{4x-24}{18-3x}$
$=\frac{-4x+24}{3x-18}$
$=\frac{-4(x-6)}{3(x-6)}$
$=-\frac{4}{3}$

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

$-\frac{4}{3}$

$\frac{4x-24}{18-3x}$
$=\frac{-4x+24}{3x-18}$
$=\frac{-4(x-6)}{3(x-6)}$
$=-\frac{4}{3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.